Analysis Of Application Of E-Filing System In Effort To Increase Corporate Taxpayer Compliance In Submission Of Period And Annual Taxation Letter At The Sumedang Tax Service Office - Merisa Nur Afipani; Ayi Srie Yuniawati; Tita Kartika (LPPM Universitas Sebelas April, 2021)
The core of the problem in this research is the implementation of e-filing and efforts to improve corporate taxpayer compliance in submitting Periodic and Annual Tax Returns (SPT) at KPP Sumedang. This study aims to determine the application of the efilling system, and to determine the efforts to improve corporate taxpayer compliance in submitting periodic and annual tax returns at KPP Pratama Sumedang. The location of the research was carried out at KPP Pratama Sumedang. This research method uses descriptive qualitative by using primary and secondary data sources. The sampling technique used purposive sampling method. Data collection methods in this study used interviews, documentation and data analysis methods. The resource persons taken in this study were 5 people. Based on the results of this study, it can be concluded that the implementation of the e-filing system is in accordance with the registration procedures based on tax regulations and has been running optimally and provides convenience for corporate taxpayers who report their notification letters, reduction in queues, savings in paper use, and ease of filing. document. Efforts to improve corporate taxpayer compliance are by conducting socialization, automatic notification via email of taxpayers regarding annual reporting obligations and administering administrative sanctions for taxpayers who do not report SPT.